(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article examines how colloquial idioms used in Jack London’s dialogues undergo semantic, stylistic, and pragmatic transformation in their Uzbek translations. The study focuses on translator strategies such as literal rendering, functional equivalence, cultural substitution, and stylistic softening, identifying how these approaches influence the preservation of communicative intent and character voice. By analyzing selected idiomatic units from London’s major works and comparing them with their Uzbek versions, the research reveals patterns of meaning shifts, degrees of domestication, and instances of expressive loss or enrichment. The findings demonstrate that while Uzbek translators generally succeed in maintaining narrative coherence and emotional tone, certain transformations reshape the original colloquial flavor due to cultural, linguistic, and stylistic constraints. The article highlights the importance of balancing naturalness and fidelity to ensure authentic representation of London’s dialogic style.